Reactions to characterisation of ethnic groups in Sarawak newspapers. - Ting, Su Hie; Collin, Jerome (2013)
Ethnic groups may be identified by ethnic group membership, language, regional affiliation, customs and other symbols of ethnicity. The study examined reactions to characterisation of ethnic groups in a leading Sarawak English daily newspaper and a leading national English daily newspaper. The ethnic groups focused on were Malay, Chinese and Sarawak indigenous communities. The specific aspects examined were: (1) portrayal of ethnic groups in newspaper headlines, and (2) reactions to portrayal of ethnic groups by members of the same community. For the study, news reports and feature articles which make explicit mention of the name of the ethnic groups were analysed to identify the collocation of topics with ethnic groups, and subsequently to draw inferences on the discursive construction of ethnic identities by the newspapers. The characterisations of the ethnic groups were presented to members of the same ethnic group to elicit their reactions. Preliminary results indicate that the reactions were on a continuum of agreement to strong disagreement with the constructed identities of ethnic groups in Sarawak as portrayed in the selected English daily newspapers. The study tapped into the latent stereotypes held by various ethnic groups and brings forward a crystallisation of acceptable and unacceptable characterisation of ethnic identities.